Cellular Mechanisms of Myocardial Depression in Porcine Septic Shock - Jarkovska, Dagmar; Markova, Michaela; Horak, Jan; Nalos, Lukas; Benes, Jan; Al-Obeidallah, Mahmoud; Tuma, Zdenek; Sviglerova, Jitka; Kuncova, Jitka; Matejovic, Martin; Stengl, Milan (Frontiers in Physiology, 2018)
The complex pathogenesis of sepsis and septic shock involves myocardial depression, the pathophysiology of which, however, remains unclear. In this study, cellular mechanisms of myocardial depression were addressed in a clinically relevant, large animal (porcine) model of sepsis and septic shock. Sepsis was induced by fecal peritonitis in 8 anesthetized, mechanically ventilated, and instrumented pigs of both sexes and continued for 24 hours. In 8 control pigs, an identical experiment but without sepsis induction was performed. In vitro analysis of cardiac function included measurements of action potentials and contractions in the right ventricle trabeculae, measurements of sarcomeric contractions, calcium transients and calcium current in isolated cardiac myocytes, and analysis of mitochondrial respiration by ultrasensitive oxygraphy. Increased values of modified Sequential Organ Failure Assessment (SOFA) score and serum lactate levels documented the development of sepsis/septic shock, accompanied by hyperdynamic circulation with high heart rate, increased cardiac output, peripheral vasodilation, and decreased stroke volume. In septic trabeculae, action potential duration was shortened and contraction force reduced. In septic cardiac myocytes, sarcomeric contractions, calcium transients, and L-type calcium current were all suppressed. Similar relaxation trajectory of the intracellular calcium-cell length phase-plane diagram indicated unchanged calcium responsiveness of myofilaments. Mitochondrial respiration was diminished through inhibition of Complex II and Complex IV. Defective calcium handling with reduced calcium current and transients, together with inhibition of mitochondrial respiration, appears to represent the dominant cellular mechanisms of myocardial depression in porcine septic shock.